Directly Printable Flexible Strain Sensors for Bending and Contact Feedback of Soft Actuators - Elgeneidy, Khaled; Neumann, Gerhard; Jackson, Michael; Lohse, Niels (Frontiers in Robotics and AI, 2018)
This paper presents a fully printable sensorised bending actuator that can be calibrated to provide reliable bending feedback and simple contact detection. A soft bending actuator following a pleated morphology, as well as a flexible resistive strain sensor, were directly 3D printed using easily accessible FDM printer hardware with a dual-extrusion tool head. The flexible sensor was directly welded to the bending actuator’s body and systematically tested to characterise and evaluate its response under variable input pressure. A signal conditioning circuit was developed to enhance the quality of the sensory feedback and flexible conductive threads were used for wiring. The sensorised actuator’s response was then calibrated using a vision system to convert the sensory readings to real bending angle values. The empirical relationship was derived using linear regression and validated at untrained input conditions to evaluate its accuracy. Furthermore, the sensorised actuator was tested in a constrained setup that prevents bending, to evaluate the potential of using the same sensor for simple contact detection by comparing the constrained response to that of the free-bending state at the same input pressure. The results of this work demonstrated how a dual-extrusion FDM printing process can be tuned to directly print highly customisable flexible strain sensors that are able to provide reliable bending feedback and basic contact detection. The addition of such sensing capability to bending actuators enhances their functionality and reliability for applications such as; controlled soft grasping, flexible wearables, and haptic devices.